Brachioproctic eroticism and transmission of retrovirus associated with acquired immune deficiency syndrome (AIDS). Issue 6 (December 1986) - Donovan, B; Tindall, B; Cooper, D
Abstract : A case of transmission of the acquired immune deficiency syndrome (AIDS) associated retrovirus (ARV) by brachioproctic eroticism is described.